Penerapan Bimbingan Konseling Islam dalam Pendidikan Seks di Youth Center Griya Muda PKBI Kota Semarang - Laeli Rachmawati (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2021)
Background: This study aims to describe how the implementation of sex education for adolescents in youth center Griya Muda PKBI Kota Semarang and analysis of Islamic counseling guidance on sex education for adolescents in Youth Center Griya Muda PKBI Kota Semarang. Method: This study is a descriptive qualitative study that aims to find out sex education for adolescents conducted by the Youth Center Griya Muda PKBI Semarang City in providing correct and accurate information to minimize premarital sex behavior, as well as efforts to prevent the transmission of HIV / AIDS for adolescents. The data collection techniques used in this study are with observations, interviews, and documentation. Results: The implementation of sex education conducted by Griya Muda Youth Center includes education and counseling services using direct and indirect methods. Judging from the analysis of Islamic counseling guidance, the objectives, methods and functions of activities carried out are close to the implementation of Islamic counseling guidance. However, youth center Griya Muda has not implemented the entire existence of Islamic counseling guidance completely.